Impact of moral distress on burn-out: a cross-sectional survey of front-line family physicians during the initial wave of the COVID-19 pandemic - John Billimek; Johanna Shapiro; Cynthia Haq; Tan Nguyen; Avital Sabrina Fischer; Reece Fenning; John Michael Robb; Allison Slater; Uyen Mai; Tien Lam; Jan Paolo De La Cruz (BMJ Open)
Objectives Primary care clinicians are especially prone to burn-out. The primary objective of this study was to investigate factors contributing to burn-out and moral distress and their relationship among practising family physicians (FPs) in California early in the COVID-19 pandemic.Design Cross-sectional study, online survey evaluating burn-out, moral distress and associated factors.Setting California FPs between July and August 2020 practising in community health centres, hospital systems, private clinics and university systems were surveyed with a 22-item online questionnaire.Participants FPs practising in California were eligible. The final sample included 218 physicians.Primary and secondary outcome measures The primary independent variable was frequency of moral distress and the primary outcome variable was worsening burn-out. Moderator variables included gender and employer support.Results FPs experiencing higher burn-out and moral distress were more likely to report concerns regarding personal COVID-19 risk and lack of personal protective equipment. Practising self-care and personal wellness were associated with decreased moral distress. Female physicians were 3.86-fold more likely to report worsening burn-out compared with male physicians. Employer support was associated with a 59% reduced burn-out risk and 54% reduction in frequent moral distress. Frequent moral distress was associated with a 3.12- fold higher burn-out risk. Gender moderated the relationship between moral distress and burn-out. Moral distress was associated with a 3.55-fold increase in burn-out risk among females.Conclusions Female FPs experienced greater levels of moral distress and burn-out than male physicians. Moral distress was differentially associated with increased burn-out among female physicians. Employer support was a protective factor against moral distress and burn-out.